3D design terrain models for construction plans and GPS control of highway construction equipment - Hanna, Awad; Hintz, Cassie; Vonderohe, Alan (National Center for Freight and Infrastructure Research and Education, 2010)
Use of Global Positioning System (GPS) technology to guide earth-moving equipment is quickly becoming common place in transportation facilities construction because it speeds project delivery and cuts costs. A requirement of this technology is a 3D representation of the design surface. Current design products for highways and other transportation facilities are 2D plans, profiles, and cross sections. To employ GPS machine guidance, these design products must be converted to 3D models prior to construction. Ironically, the technology used for producing 2D plans is often capable of 3D outputs. This research is intended to aid transportation organizations in developing strategies to overcome institutional, cultural, and legal impediments to adoption of 3D design and creation of more seamless data and work flows from design through construction. The full potential of new, spatial technologies to increase efficiencies in transportation facilities delivery cannot be realized without addressing these issues. The objectives of this project are to: 1) Describe the state of the art in adoption of 3D transportation design and construction technologies; 2) describe potential benefits and productivity gains of utility of 3D technologies in transportation design and construction; 3) identify and characterize technological, institutional, cultural, and legal impediments to adoption of 3D design/construct technologies; 4) suggest strategies to overcome identified impediments; 5) incorporate aspects of this research in the educational program of the Department of Civil and Environmental Engineering at UW-Madison.
109 p.
Keywords: Cost effectiveness; State of the art; Three dimensional displays; Construction equipment; Road construction; Global Positioning System